Urgensi Penerapan Metode Pembiasaan Dalam Pembelajaran Materi Keislaman Perspektif Behavioristik: Studi pada SMA ‘Aisyiyah Boarding School Malang - M. Taufiqi Rachman; Fathor Rahim; Dina Mardiana (Universitas Muhammadiyah Prof Dr Hamka, 2022)
This study aims to: (1). Describe the urgency of the implementation of Islamic education learning in SMA ‘Aisyiyah Boarding School (ABSM) Malang; (2). Find out the impact of applying the habituation method in learning Islamic material to students, and (3). Analyze the learning process from the perspective of behavioristic learning theory. This research uses qualitative methods and the type of descriptive analysis. Sources of data taken from school principals, madrasah diniyah teachers, and students. This study used several methods to obtain data, namely unstructured interviews, direct observation, and documentation. Data analysis technique uses interactive models by Miles, Huberman, and Saldana which includes data condensation, data presentation and conclusion. The results of this research showed (1). The implementation of the habituation method in learning Islamic material at SMA ABSM is really urgent for the effectiveness and efficiency of learning; (2). The implementation of intense habituation methods in learning Islamic material had positive implications for the behavior and psychology of students; (3). The process of learning Islamic material in SMA ABSM using the habituation method in accordance with the principles of behavioristic learning.